Angioembolization for post-traumatic renal arteriovenous malformations - Francis Sridhar Katumalla; Aparajita Sophia D'souza; Rajneesh Calton; Kim Jacob Mammen (Wolters Kluwer Medknow Publications, 2015)
The risk of renal arteriovenous malformations (AVMs) must be kept in mind as a cause as sudden hematuria in patients with previous renal injury. Treatment of renal AVMs has evolved from nephrectomy to angioembolization, as it allows good control bleeding while preserving maximum renal function and appears to be the first treatment of choice. Hence, angioembolization facilities must be available in centers dealing with renal trauma.